Analysis of Bank Health Levels Through Pre-Pandemic and During Pandemic at PT. Bank Central Asia, Tbk for the Period 2018-2022 With a Risk-Based Bank Rating (RBBR) Approach - Uky Chesya Virtanya; Ira Phajar Lestari; Zaidatun Ekastuti; Sudarsono Sudarsono; Bertilia Lina Kusrina (Dinasti Publisher, 2023)
The purpose of this research is to evaluate the health levels of PT Bank Central Asia Tbk before the pandemic in the period of 2018-2019 and during the pandemic in the period of 2020-2022 using the RBRR method. This study employed a quantitative research design with secondary data obtained from the annual reports on BCA official website. The data collection techniques used were documentation and library research. The analysis technique used is quantitative descriptive analysis. The results showed that PT Bank Central Asia was in the very healthy category during the period 2018 to 2022.. It can be seen from indicators such as NPL and LDR, which show that the bank has successfully managed the risks effectively. In addition, the GCG assessment also shows the implementation of good corporate governance. The calculations of ROA and NIM show that the bank has achieved excellent profitability. Furthermore, the calculation of CAR indicates that the bank has been effectively managed the capital. Therefore, PT Bank Central Asia is considered capable of dealing with negative influences and risks through before and during the pandemic.